From Engagement to Empowerment: Transformative Ecological Citizenship among the Tengger Indigenous Community through Tri Hita Karana Local Wisdom - Triyanto Triyanto; Widya Noventari; Bariq Maulana; Siska Fitri Anggraheni; Mohd Hairy Ibrahim (Jurnal Pemberdayaan Masyarakat, 2025)
This research explores how the Tengger indigenous community in Indonesia practices a transformative model of ecological citizenship, rooted in the local cosmology of Tri Hita Karana, which integrates harmony between humans, nature, and God. In response to the growing global attention to community-based environmental governance, this study aims to analyse how spiritual and cultural practices among the Tengger people shape sustainable ecological behaviour and collective resource management. Using a participatory ethnographic approach, the research engaged seven key informants, including dukun adat (traditional leaders), youth, women's groups, and local government representatives. Data were collected through in-depth interviews, participatory observations, and document analysis to capture the community's everyday ecological practices and moral reasoning. The findings reveal that rituals such as Yadnya Kasada, along with collective practices like forest protection and water management, are legitimized through sacred values and customary norms that sustain environmental stewardship. Moreover, the increasing participation of youth and women in ecological education and sustainable livelihood programs signifies a shift towards inclusive and participatory governance. This study contributes to the theoretical development of indigenous-based ecological citizenship by conceptualizing it as a vernacular, spiritually grounded, and participatory model of environmental governance that bridges local cosmology with global sustainability frameworks.